Voluntary System: The Legal Problems of Zakat Management For The Fulfillment of Socio-Economic Justice - Zainuddin, Zainuddin; Aan Aswari; Salle (Yuridika, 2023)
Zakat is primarily an economic instrument used to achieve socio-economic justice. This goal can be accomplished if management is done properly and correctly. The purpose of this article is to analyze the legal policy of zakat management with the model of the voluntary system and its implications for the realization of social and economic justice in the community. This research is normative legal research with primary legal sources in the form of laws and regulations related to zakat management legal policies, which are then analyzed descriptively and qualitatively. According to the findings of the study, the legal policy of zakat management with a voluntary system model is based on the principle of community volunteerism in zakat payment. This voluntary system model is heavily reliant on public legal awareness regarding zakat payment. The use of the voluntary system model has consequences for the community's non-optimal fulfillment of social and economic justice, which is caused by a lack of state involvement through legal policies. The state's role is required to enforce the zakat law by compelling zakat obligors to fulfill their obligations. On the other hand, the potential for zakat remains enormous, and it must be managed optimally.